Menjalin Persaudaraan dalam Terang Iman: Semangat Gotong Royong Dayak Wehea di Tengah Pelayanan Umat Paroki St. Maria Ratu Damai Nehas Liah Bing - Gregorius Rivaldo Junior (Perspektif, 2026)
The article entitled "Establishing Brotherhood in the Light of Faith: The Spirit of Gotong Royong Dayak Wehea in the Service of the Parishioners of St. Maria Ratu Damai Nehas Liah Bing” highlights the integration of local cultural values and the spirit of Christian faith in church life. Gotong royong, as a cultural heritage of the Dayak Wehea tribe, is not only a pattern of community life, but also a collective force that sustains the service and involvement of the people in various pastoral activities in the parish. Through a reflective and contextual approach, this paper highlights how the Church is present not only as a messenger of faith, but also as a protector of noble cultural values that support the realization of true brotherhood. The integration of gotong royong and the teachings of Christ's love shows that culture and faith can work in harmony, enrich each other, and become the basis of the spirituality of living together. Thus, people are invited to build a living Church, rooted in culture, and based on love, service, and solidarity as a tangible manifestation of brotherhood in the light of faith.